PENGARUH HARGA JUAL, BIAYA PROMOSI DAN BIAYA DISTRIBUSI TERHADAP VOLUME PENJUALAN PT. SINDOKANOMAN TEKNIK INDONESIA - Amin Nurfuji Faozaan dan Bambang Bernanthos (Jurnal Manajemen FE-UB, 2017)
Based on the data of material sales / goods in PT. Sindokanoman Teknik Indonesia in 2010 to 2016 there is an increase and there is a decrease. In 2010 the volume of penjulan of Rp 1,689,500, in 2011 rose by 6.42% by Rp 1.798.000.000 in 2012 rose 8.62% amounting to Rp 1,953,000,000, in year 2013 increased by 21.25% to Rp 2,368,000,000, from 2010 until 2013 always increased. Significant increase occurred from 2012 to 2013 at 21.25%. However, in the following years there will be a decline until the end of 2016. That is 2014 sales volume of 1.968 million decreased 16.89%, in 2015 amounted to 1.792 million decreased 8.94%, and last year 2016 amounting to Rp 1,488,000,000, down 16.96%.          Based on the results of tests and analysts that the authors do by using SPSS 23 can be concludedthat analysis of selling price, cost of promotion and distribution costswhadapa sales volume onPT. Sindokanoman Teknik Indonesiadapatdikatakanberhasil for the year 2010 to 2013.Akan but there is a problem that happened is the decrease in sales volume from 2014 to 2016, this decline occurs because there are other factors beyond the variable that the author conveyed. Keywords: Price, Promotion, Distribution and Sales